Finite element analysis on post-buckling of thin-walled structures using ANSYS - Theint, Yi Mon (2015)
This project aims to develop a standard design procedure to simulate the buckling and post-buckling behaviour of thin-walled structures, via the use of finite element analysis, and hence determine conservative estimates of the ultimate compressive load. The finite element program, ANSYS (academic version 15.0) was used in this study. This report is a continuation of previous studies under the same name, and documents the design procedure that was developed as well as new improvements made to it. To validate the robustness of the design procedure, specimens of two different cross sections were tested in this study, namely the lipped column with concentric and eccentric loading conditions, and the hollow box sections. During the course of verification for lipped column of previous study, it was discovered that there was an error in location of the neutral axis which would affect the loading location and revisions were done to ensure accurate and complete coverage of the current and previous specimens. The results obtained were checked against experimental data and led to the development and the revision of design procedures for the pin-ended lipped column and hollow box section.